Corbelled Buildings as heritage resources: in the Karoo, South Africa - Hancock, Caroline (Conservation of the Built Environment, 2019)
The primary aim of this study was to determine who claims the corbelled buildings in the Karoo as their heritage and why. Through the use of vernacular architecture and heritage identification theory, interviews and research it is clear that the buildings are significant and a heritage resource. Their significance lies in their historical, social, aesthetic, symbolic and cultural values, as well as their unique vernacular construction and limited distribution. The corbelled buildings as vernacular buildings are part of the natural landscape which the local community associate as part of their identity and heritage. The buildings also possess academic and historical potential as they have the potential through further archaeological and vernacular architectural research, to provide more information on the northern frontier during the late 18th and early 19th centuries, a time that is not well recorded or documented. The buildings were built in 19th century along the ‘open’ northern frontier where there was intermingling and creolisation of people from different economic and social groups. As a result, they cannot be claimed by a single group of people in the present. The vast range in types and styles of corbelled buildings indicate that they were built by most people living in the area. They can therefore, be claimed by everyone who lives in the area today. They can also be claimed as national heritage as they possess values that are common to the whole country.